2020
DOI: 10.1016/j.heliyon.2020.e05192
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect of pomegranate juice against chemically induced bladder cancer: An experimental study

Abstract: Objectives Pomegranate juice (PJ) is rich in important compounds with anti-cancer activities. This study aims to investigate the preventive effect of pomegranate juice (PJ) against bladder cancer (BC). Methods Eighty male Sprague Dawley rats were randomly classified into 4 equal groups: (1) Normal controls; (2) PJ group: supplied by PJ for 12 weeks; (3) Cancer-induced group: intake 0.05% v/v N -butyl- N -(4-hydroxybu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 53 publications
(61 reference statements)
1
9
0
Order By: Relevance
“…The next in vivo study confirmed the beneficial effect of pomegranate juice in reducing hyperplasia, dysplasia, and invasive neoplasms in the chemically induced ( N -butyl- N -(4-hydroxybutyl)-nitrosamine) BC rat model [ 69 ]. Rats with chemically induced BC were characterized by p53 expression impairment, while pomegranate juice treatment restored a regular p53 expression.…”
Section: Pomegranatementioning
confidence: 80%
See 3 more Smart Citations
“…The next in vivo study confirmed the beneficial effect of pomegranate juice in reducing hyperplasia, dysplasia, and invasive neoplasms in the chemically induced ( N -butyl- N -(4-hydroxybutyl)-nitrosamine) BC rat model [ 69 ]. Rats with chemically induced BC were characterized by p53 expression impairment, while pomegranate juice treatment restored a regular p53 expression.…”
Section: Pomegranatementioning
confidence: 80%
“…A summary of the anticancer effects and mechanisms of pomegranate action is presented in Figure 1. cell proliferation [41], glycolysis [53][54][55], and cell cycle [59,60] as well as apoptosis [23,41,42,47,48,51,53,54,61,62,69,71]. The summary of anticancer effects and mechanisms of pomegranate action.…”
Section: Pomegranate In Bladder Cancer Preventionmentioning
confidence: 99%
See 2 more Smart Citations
“…It can correct the expression of pro-inflammatory cytokines (interleukin 6 and hypoxia-inducible factor 1), it also press angiogenesis by downregulation of hypoxia-inducible factor and supports apoptosis through reduction of the tumor suppressor gene p53. Mortada et al (2020) n. Dwarf pomegranate extracts showed potent growth inhibitory activities in human prostate cancer cells (DU145), which appear to be mediated by a pro-apoptotic mechanism. reduced hs-CRP, IL-6, and TNF-α.…”
Section: Minaiyan Et Al (2014) Alzheimermentioning
confidence: 99%